Implementing TOGAF for Strategic Sustainability in the Food and Beverage Industry - Hajar Dewantara; Nur Astaman Putra; Ilham Abu (Global Research and Collaboration, 2024)
PT. Greenfields Indonesia is a prominent company in the food and beverage industry, specializing in the production and distribution of premium fresh milk products. The company is committed to delivering high-quality dairy offerings, including fresh milk, yogurt, and other dairy derivatives, while adhering to international standards. In alignment with its vision and mission, PT. Greenfields Indonesia actively promotes sustainable agriculture by partnering with local farmers, improving their welfare, and fostering environmentally responsible practices. To enhance its operational efficiency and strategic alignment, PT. Greenfields Indonesia leverages enterprise architecture frameworks, such as TOGAF (The Open Group Architecture Framework). The adoption of TOGAF supports the company in optimizing its business processes, technology integration, and resource allocation to achieve long-term sustainability goals. Furthermore, the company conducts impactful corporate social responsibility programs, focusing on environmental conservation, educational support, and community health initiatives. These efforts underscore PT. Greenfields Indonesia's dedication to creating value for society and the environment while ensuring sustainable business growth.